A STUDY OF METAPHORS USED IN “A CHRISTMAS CAROL” BY CHARLES DICKENS / Vu Phuong Anh; Supervisor: Nguyen Thi Van Dong. Dr. - Vu, Phuong Anh
This thesis, entitled “A study of metaphors used in “A Christmas Carol” by Charles Dickens, discusses the issue of metaphor in linguistics. Based on studies, metaphors make linguistics, literature more expressive and colorful. The thesis analyzes written work focusing on metaphors that have been produced in the previous century, including both foreign and native research works on linguistics. The purpose of this analysis is to gain an in-depth understanding of the role metaphor plays and what the metaphor could mean for linguistics. Based on the framework of E. Slave, R. Galperin and Galdi, metaphor in this thesis will be analyzed by part of speech, novelty, structure and presence of departure and arrival terms. Besides using qualitative and quantitative methods to provide accurate statistics and analytical methods to give the most overview of the metaphor. There are many metaphors in poetry, verses and songs, but to have a novella with metaphors like "A Christmas Carol" by Charles Dickens is undiscovered! Therefore, with the most general theories of metaphor (definition, classification, form) and novella (definition, classification, form), we have an objective view of the necessary information in this thesis. In order to explore the figure of speech in the novella “A Christmas Carol” by Charles Dickens. The formative elements in the work will be analyzed, followed by: Characters and point of view. The thesis will be processed following the checklist of linguistic devices. Features of metaphor are concerned mostly in chapter 2 and clarified in the usage within chapter 3. Thus, the metaphor in "A Christmas Carol" serves as a foundation for analysis in literature in general and in short fiction in particular, as well as to clarify the nature of some preferable metaphol